PhET Simulations Improve Fraction Learning in Primary School Students - kukuh imam setyawan Kukuh; Bagus Ardi Saputro Bagus; Arfilia Wijayanti Arfilia; Marvin Valdez Tandas (Universitas Pendidikan Ganesha, 2025)
Teaching fractions in elementary school often presents challenges, particularly when conventional instructional methods are used, as many students struggle to develop a deep understanding of mathematical concepts. This study aims to explore students’ responses and comprehension regarding the effectiveness of fraction learning using PhET (Physics Education Technology) simulations integrated with a visual project based learning approach. The research employed a qualitative design with third-grade students as the sample. Data were collected through participatory observations, student worksheets, and daily assessments covering three learning outcomes: fraction recognition, fraction comparison, and fraction ordering. Data were analyzed descriptively and qualitatively to evaluate success rates, patterns of student responses, and cognitive strategies. The results indicate a progressive improvement in learning outcomes, with success rates of 46.15% for fraction recognition, 66.66% for fraction comparison, and 70% for fraction ordering. The integration of PhET simulations with visual project-based learning effectively promoted conceptual understanding, creativity, and active student engagement, although some students still faced difficulties transitioning from visual representations to symbolic forms. These findings imply that systematic use of interactive simulations can serve as an effective instructional strategy to enhance conceptual understanding, critical thinking, and creativity in elementary mathematics education.